Residual efficacy of cypermethrin and pirimiphos-methyl against Sitophilus granarius (L.) and Plodia interpunctella (Hübner) on concrete surface - Andrić, Goran G; Kljajić, Petar J; Pražić Golić, Marijana P (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Residual activity of EC formulations of two insecticides, cypermethrin (combined withthe synergist piperonyl butoxide) and pirimiphos-methyl, against Sitophilus granarius (L.)adults and Plodia interpunctella (Hübner) larvae was investigated on concrete surface. The experiment was run indoors at 16-24ºC temperature and 30-60% r.h. by applying water solutions of products based on cypermethrin (48 mg AI/m2) and pirimiphos-methyl (750 mg AI/m2) to concrete surface. Insect mortality was estimated after 2, 7 and 14 days of insect exposure to treated concrete and 7 days of recovery on untreated coarse wheat meal at 24-26ºC and 55-65% r.h in the laboratory.High efficacy of cypermethrin against S. granarius adults (87-100%) and P. interpunctellalarvae (84-100%) was detected after 14 days of exposure to all deposits on concrete surface. Pirimiphos-methyl achieved maximum efficacy (100%) in all treatments of S. granarius adults and P. interpunctella larvae after 2 and 14 days of exposure, regardless of deposit age. After 7 days of recovery, the efficacy of both insecticides mostly increased, especially of cypermethrin, up to around 50% after two days of exposure, up to 24-45% after seven days of exposure and up to 15% after 14 days of exposure. The results show that the EC formulations of cypermethrin and especially of pirimiphos-methyl were highly effective in controlling S. granarius adults and P. interpunctella larvae over a period of 60 days following application to concrete surface.
Keywords: Cypermethrin; Pirimiphos methyl; Residual efficacy; Concrete; Sitophilus granarius; Plodia interpunctella